The Timing of Out-of-Court Settlements Revisited: Theory and Cross- Sectional Evidence from Texas since 1988 - Jun Zhou (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Legal institutions play an important role in affecting delay in settlement. But little research has investigated the institutional causes of delay. The empirical literature is ambiguous regarding the impact of trial-court delay on settlement delay. I analyze the timing of bargaining and the causes of delay using a cross-section of insurance claims in Texas over a 20-year span. I discuss a dynamic model of pretrial negotiation to illustrate how changes in the legal systems might affect the duration of settlement. Comparative statics results are then corroborated with empirical estimates of a hazard function adjusted to account for the heterogeneity of claims and the time dependence suggested by theory. Statistical tests are consistent with the theoretic prediction that delay in trial courts expedites out-of-court settlement. I also find that alternative dispute resolution, a legal process designed to save transaction costs, reduces the rapidity of settlement. Prejudgement interest, a law introduced to reduce delay, actually causes a greater delay in settlement. The results have implications for efficiency of the judicial system and reform efforts aiming to reduce delay.
urn:nbn:de:bvb:19-epub-13207-9
Keywords: K41; 330; settlement delay; trial-court delay; prejudgment interest; alternative dispute resolution; Zivilprozess; Schiedsgerichtsbarkeit; Verhandlungstheorie; Zeitökonomie; Theorie; Schätzung; Texas